Game Theory and Mutual Misunderstanding Scientific Dialogues in Five Acts - Mamoru Kaneku. (Institute of Policy and Planning Sciences, 2003)
A mere instance of thought leads to great achievements Great plans and huge amounts of labor lead to scattered results Only tcn kilometers of opaque air make heat and water circulate Another 200 kilometers higher the clear air drifts Turbid seawater near the shore gives birth to fish Transparent ocean water flows as a current A mere moment in life has meaning For the rest, people work consciously in a dream